THE CIVIL LIABILITY OF A FOOTBALL PLAYER THAT WOUNDS AN OPPONENT AT A CRITICAL MOMENT OF THE GAME - Abreu, Gustavo Albano (Revista dos Estudantes de Direito da Universidade de Brasília, 2016)
I - Introduction. II - Historical evolution of the civil liability as regards wounds between sportsmen. III - The most known decisions in Argentine Jurisprudence in the matter of wounds between sportsmen at a critical moment of the game. Cases “Cottroneo vs Banfield”; “Berman vs Goldin”; “Telechea vs Beldrio”; “Gil Osvaldo vs Sociedad de Fomento”; and “Pizzo vs Camoronesi”. IV - The State authorization in football. V - The assumption of risks in football. VI - By way of conclusion.